PEMBERDAYAAN MASYARAKAT DALAM PENANGGULANGAN HIV/AIDS DI KOTA SEMARANG (STUDI PADA KELOMPOK : WARGA PEDULI AIDS KELURAHAN PETERONGAN KECAMATAN SEMARANG SELATAN KOTA SEMARANG - Arif Abdul Majid; Achmad Taufiq; Rina Martini (Journal of Politic and Government Studies, 2015)
Nowdays, handling of HIV/AIDS is not only concerned with health problems, but also we have to deal with social matters. Community empowerment is a new approach to handle the problem of HIV and AIDS and to eliminate discrimination against people with AIDS. An empowerment of people care for AIDS is called Warga Peduli AIDS Kelurahan Peterongan. By the presence of Warga Peduli AIDS Kelurahan Peterongan, there will be no discrimination against people with AIDS and residents who have highly risked of HIV contagion could be financially independent. Through this research, writer explains the process of community empowerment by a group of Warga Peduli AIDS Kelurahan Peterongan and explains the support and inhibitors factors of process of empowerment by a group of Warga Peduli AIDS Kelurahan Peterongan. In this research writer uses interview and study documentation method to get data. Result shows no discrimination toward people with AIDS and people who have highly risked of HIV contagion. The support factors of empowerment by a group of Warga Peduli AIDS Kelurahan Peterongan are the financial support of governments and NGO’s, better communication and easy access to information. While the barrier factors are lack of knowledge, lack of education and lack of funding sources. Additionally, the government should provides larger budget for the suistainability of the empowernment of Warga Peduli AIDS Kelurahan Peterongan. On the other side the members of Warga Peduli AIDS Kelurahan Peterongan should be more creative to solve every problem they have. Keywords : Handling of HIV/AIDS, Community emporwerment, WPA Kelurahan Peterongan.